Why Popularity is Not Enough: Identity-Based Drivers of Green Purchase Value among Gen Z Consumers - Naufal Dzakwana Muhammad; Agung Winarno; Fuad Abdul Fattah; Feri Dwi Riyanto; Rizka Fatkhin Nisa (Fakultas Ekonomi Universitas Kadiri, 2026)
The objective of this study is to understand the psychological mechanisms that affect green purchase value and willingness to pay more for green household products among Gen Z consumers in Indonesia, using the bandwagon effect and the need for uniqueness. This study used a quantitative approach, and 344 respondents were collected with the condition that Generation Z have experience purchasing, or care about green household products, and data was analyzed with PLS-SEM. The outcome is bandwagon effect has no affect on the green purchase value household products, while need for uniqueness has a affect. The green purchase value was proven to have a strong effect on the willingness to pay more. Furthermore, environmental self-efficacy negatively moderated the relationship between bandwagon effect and green purchase value and strengthened the relationship between need for uniqueness and green purchase value. By mapping the green consumption patterns of Generation Z in developing countries, we can see that individual-based mechanisms still play an important role, although they will differ from the surrounding social norms